Determiners as modified pronouns - Luján, Marta (Círculo de Lingüística Aplicada a la Comunicación, 2023)
This paper1 challenges the notion that the structure of the Determiner Phrase (DP) contains a virtual category which answers for DPs’ referential and anaphoric uses. Some current DP proposals, for instance, assume a null pronoun to account for the nominalized Adj(ective) in Romance, while others in Germanic postulate an abstract operator (or demonstrative) to derive the specificity of definite DPs. Such accounts strip the D(eterminer) of denotative function, turning it into a mere locus for Agreement and Case features. Moreover, they run afoul of an important notion which laid the foundation for the DP analysis. This is the hypothesis that D is a variant form of P(ronoun). For instance, Postal (1969) equates the definite D with the third-person P, as do earlier grammarians like Bello (1847) and Jespersen (1924), who further identify it as a Dem(onstrative). If these authors are on the right track, it would appear that the definite D already has the attributes that the null categories in the current DP proposals are trying to capture.